Better Performance Prospect of Large-Medium Enterprises: The Role of Innovation - Rapita Handayani; Rossanto Dwi Handoyo (Journal of Economics, Business, and Accountancy Ventura, 2019)
Based on the Business Characteristics Survey 2019 conducted by Statistics Indonesia, enterprises developed innovation are only 11.65%. Although innovation provides the benefit of a significant increase in revenue, there are 63.44% of companies that do not innovate. Therefore, it is necessary to study the effect of innovation on the prospects of large and medium-sized businesses in Indonesia. This study also observed the innovation types and business characteristics of large-medium enterprises. The data processed in this study came from the micro-data of 312,080 large-medium enterprises resulting from the 2016 Census of Economic-Advanced Data Collection for Large-Medium Enterprises and Micro-Small Enterprises. It was carried out by Statistics Indonesia in 2017 in 34 provinces in Indonesia. The method used to analyze the data was Logistic Regression. The result of the study showed that marketing innovations and product innovations were the most innovative types widely carried out by large-medium enterprises. The effect of innovation variable was seen in categories of manufacturing; water supply, sewerage, waste management & remediation; construction, transportation & storage; financial & insurance; and human health & social work. These categories will have better business prospects when there are more types of business innovations implemented. These suggest that leaders of large-medium enterprises and related stakeholders engaged in these sectors to pay more attention to innovation factors and their indicators in the operation of enterprises.